2010
DOI: 10.1002/ajpa.21222
|View full text |Cite
|
Sign up to set email alerts
|

Brief communication: Tissue isotopic enrichment associated with growth depression in a pig: Implications for archaeology and ecology

Abstract: Stressors such as fasting or poor diet quality are thought to potentially alter the nitrogen and carbon isotopic values of animal tissues. In this study, we demonstrate an inverse correlation between growth rate and multiple tissue enrichment of delta(15)N, delta(13)C, and, to a lesser degree, delta(18)O in a juvenile pig. A more complex pattern is observed with respect to tissue deltaD and growth rate. The observed association between growth rate and tissue isotopic fractionation has important implications fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 74 publications
1
54
0
Order By: Relevance
“…While previous studies have quantified, with some notable disagreement, D 15 N protein-collagen (DeNiro and Epstein, 1981;Schoeninger and DeNiro, 1984;Schoeninger, 1985;Hare et al, 1991;Schoeller, 1999;Ambrose, 2000;Sponheimer et al, 2003;Howland et al, 2003;Hedges and Reynard, 2007;Warinner and Tuross, 2010;O'Connell et al, 2012), and D…”
Section: Discussionmentioning
confidence: 95%
“…While previous studies have quantified, with some notable disagreement, D 15 N protein-collagen (DeNiro and Epstein, 1981;Schoeninger and DeNiro, 1984;Schoeninger, 1985;Hare et al, 1991;Schoeller, 1999;Ambrose, 2000;Sponheimer et al, 2003;Howland et al, 2003;Hedges and Reynard, 2007;Warinner and Tuross, 2010;O'Connell et al, 2012), and D…”
Section: Discussionmentioning
confidence: 95%
“…The research showed that the oxygen isotope level in tooth enamel does not change with age in rats (a rat's teeth grow throughout its life). Moreover, an analysis of the oxygen isotope level in the bone apatite of pigs conducted by Warinner and Tuross (2010) showed that there was no significant difference in the δ…”
Section: Discussionmentioning
confidence: 99%
“…Body water comprises a pool of stable oxygen isotopes incorporated into the structure of all the tissues of living organisms, including bones and teeth (White et al, 2004b;Warinner and Tuross, 2010;Wolf et al, 2011). In skeletal tissue, oxygen incorporated into the inorganic matter, mainly occurs in the form of phosphate, carbonate and hydroxide ions (Kohn and Cerling, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…4.7), using fish and mammal muscle (diet)-collagen data amalgamated from different studies (DeNiro andEpstein, 1978, 1981;Sealy et al, 1987;Tieszen and Fagre, 1993;Tuross, 2009, 2010;Wright, 1994), revealed different fractionation factors, in particular depleted (negative) values for nitrogen (average Dd 13 C diet-col ¼ 3.5 for fish, 2.0 for mammals and average Dd 15 N diet-col ¼ À1.5 for fish, À0.1 for mammals). Other diet-specific studies (Howland et al, 2003;Warinner and Tuross, 2010) have also indicated variable Dd 13 C dietcol , Dd 15 N diet-col values, leading to the conclusion that a "non-static" diet-col isotope offset employment is perhaps the best strategy when attempting to reconstruct paleodiets of cultures consuming varied foods.…”
Section: Established a Distinct Relationship Between Different Animalmentioning
confidence: 93%
“…Following the work by Hare et al (1991) and , and utilizing literature-mined data (Hare et al, 1991;Howland et al, 2003;Warinner and Tuross, 2010), we derived Dd 13 C diet-col and Dd 15 N diet-col estimates for C 3 /C 4 plant mixed (pig) diets (Fig. 2).…”
Section: Established a Distinct Relationship Between Different Animalmentioning
confidence: 99%